Index of Research Access: an estimate of travel accessibility for research - Meneses K; McNees P (Dove Medical Press, 2012)
Patrick McNees,1,3 Karen Meneses21School of Health Professions, 2School of Nursing, University of Alabama at Birmingham, 3Kirchner Private Capital Group, Birmingham, Alabama, USAAbstract: There is a paucity of methods that examine the relative difficulty or ease of access to research. The Index of Research Access was designed to provide a quantitative index allowing a determination of the probable ease or difficulty in accessing research participation for either an individual compared to a reference group, or for a group of individuals compared to another group or reference group. The aims of this paper are to (1) describe the major factors considered in the development of the Index of Research Access, an index of research accessibility; (2) provide the rationale and formula for the Index of Research Access; (3) describe the testing and application of the Index of Research Access using a sample of 239 women participating in a longitudinal trial of psychoeducational support interventions for breast cancer survivors; and (4) consider implications of the Index of Research Access for other research endeavors.Keywords: methodology, distance barrier, travel barrier, research barrier